Vantage point : the sixth estate and other discoveries - Teodoro, Luis V., 1941- (Diliman, Quezon City : University of the Philippines Press, 2014)
Collection of essays on the Philippine political, social and economic condition.
Cynics and colonials -- Teachers and taught -- Weapons of war -- Their way of life -- Knowing the enemy -- Fiddlers by the Pasig -- Destroyer of worlds.
Keywords: PHILIPPINES -- POLITICS AND GOVERNMENT -- 20TH CENTURY; PHILIPPINES -- SOCIAL CONDITIONS -- 20TH CENTURY; PHILIPPINES -- ECONOMIC CONDITIONS -- 20TH CENTURY